A utilização das análises mecânicas e reológicas no desenvolvimento de sistemas bioadesivos termorresponsivos - Ferreira, Sabrina Barbosa de Souza (2015)
The development of binary polymeric systems, or polymeric blends, containing bioadhesive and termorresponsible polymers provides new drug delivery systems. The caracterization of these polymeric blends is an important phase that enables and understands the in vivo behavior of termorresponsible bioadhesive polymeric systems. The physical properties achievement of semisolid systems has been performed by a range of techniques, such as continuous shear reometry, oscillatory reometry and mechanical analysis (for example, texture profile analysis, softness, mucoadhesion). The aim of this study was to assess the significance and the information provided by rheological and mechanical analysis in the characterization of termorresponsible bioadhesive polymeric systems. Therefore, some ratio of polymeric blends was developed and characterized, composed by poloxamer 407 and Carbopol 971P® or Carbopol 974P® or polycarbophil. The polymeric systems were evaluated by texture profile analysis, mucoadhesion and determination of softness and the results were greater in preparations containing 20% (w/w) poloxamer 407. Besides, the continuous shear rheometry and oscillatory rheometry were performed, in addition to determining the gelation temperature in polymeric systems containing poloxamer 407 and Carbopol 971P®. Through these analyzes it was possible to verify the plastic flow with various degrees of thixotropy and yield value, besides the viscoelastic behavior. And the gelling temperatures of preparations ranged from 27.17 to 41.09 °C. It was also found that low carbomer concentration were enough to provide positive interaction parameter, however the highest values were obtained in the polimeric blends with higher concentration of poloxamer 407. Thus, the mechanical and rheological information could determine the interaction between the polymers belonging to the systems and to simulate the in vivo behavior of preparations.